Anisotropic propagation of weak discontinuities in flows of thermally conducting and dissociating gases - Tewari T.N.; Gaur M.; Ram R. (My University, 2025)
The object of the present investigation is to study the anisotropic propagation of weak discontinuities in flows of thermally conducting and dissociating gases. The velocity of propagation of the wave frcnt is determined. A set of differential equations governing the growth and decay of weak discontinuities are obtained and solved. It is found that if the sonic wave is a compressive wave of order 1, then it terminates into a shock wave after a critical time tc which has been determined. It is also observed that the effects of heat conduction and dissociation are to decrease the duration of time by which a weak discontinuity will generate into a shock wave. © 1976 Indian Academy of Sciences.